2017
DOI: 10.1097/icl.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Serum Eye Drops Combined With Silicone Hydrogen Lenses for the Treatment of Postinfectious Corneal Persistent Epithelial Defects

Abstract: The combined use of silicone hydrogel CLs and ASEs can successfully treat postinfectious corneal PEDs and prevent continuous corneal melting during acute disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The application of bandage contact lens can help these patients open their eyes and function normally [27]. Combining the epitheliotrophic effects of autologous serum and the mechanical benefits of newer hydrogel SCLs is likely to have synergetic effects on corneal epithelial wound healing, especially for recalcitrant corneal epithelial defects [3,4,6,27]. In the present study, we found that none of the patients in the continued ASE use group had epithelial defect recurrence while half of the patients (five eyes, 50%) without continued ASE use had epithelial defect recurrence during follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The application of bandage contact lens can help these patients open their eyes and function normally [27]. Combining the epitheliotrophic effects of autologous serum and the mechanical benefits of newer hydrogel SCLs is likely to have synergetic effects on corneal epithelial wound healing, especially for recalcitrant corneal epithelial defects [3,4,6,27]. In the present study, we found that none of the patients in the continued ASE use group had epithelial defect recurrence while half of the patients (five eyes, 50%) without continued ASE use had epithelial defect recurrence during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with corneal PEDs after infectious corneal ulcers, corneal scrapings for culture were obtained and the corneal ulcers were initially managed with topical antibiotic eye drops until the infiltrates resolved without active infection noted and repeat corneal cultures showed negative results. However, the lesions failed to epithelialize with progressive corneal stromal melting observed despite conventional therapeutic modalities [4]. All patients were informed regarding the advantages, disadvantages, and potential side effects of this modality, as well as the possible risks of the procedure and informed consents have been obtained from the participants.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 3 more Smart Citations